PERAN KEDOKTERAN KELUARGA DALAM MENGATASI TANTANGAN KESEHATAN MODERN : ANALISIS KONSEPTUAL: PERAN KEDOKTERAN KELUARGA DALAM MENGATASI TANTANGAN KESEHATAN MODERN : ANALISIS KONSEPTUAL - M.Raisya Kesha rakes (Yayasan Pendidikan Medika Indonesia, 2026)
Patient Mrs. K came to the elderly clinic of Muara Batu Community Health Center complaining of frequent tingling in both legs for 2 years and worsening in the past 2 months. The complaints were erratic, sometimes appearing during activity and sometimes even while resting. The patient also complained of feeling weak and dizzy when her blood sugar levels were high. The patient did not use insulin and did not regularly take Glimepiride. Primary data were obtained through auto-anamnesis and physical examination by conducting home visits, filling out family folders, and completing patient files. The assessment was based on a holistic diagnosis at the beginning, process, and end of the visit quantitatively and qualitatively. Interventions included educating her family about the causes of diabetes mellitus, educating them about lifestyle modifications and managing the disease, and explaining potential complications of the disease so that patients would take medication regularly and take preventive measures.